Anthropometric and Physical Determinants as Predictors of Playing Position in Youth Football Players - Mohammed Farhan Khalbas (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aims to investigate the relationship between anthropometric and physical characteristics and the possibility of using them as a tool to predict suitable playing positions for youth soccer players. The study used a predictive correlation design involving aging young football players. Anthropometric variables (height, body mass, body mass index, and body fat percentage) and physical performance variables (speed, agility, muscle strength, and endurance) were collected to predict the most suitable playing position. This study relies on the analysis of characteristics such as height, weight, body fat percentage, muscle strength, speed, and endurance, and the extent to which they relate to the requirements of different playing positions on the field. The results show a clear relationship between certain physical characteristics and playing positions. Goalkeepers and defenders require different anthropometric characteristics compared to midfielders and forwards. The results of the study show that most of the players are in the medium category based on the empirical norms developed. Correlation analysis showed a very strong positive relationship between height and body weight (r = 0.984), BMI (r = 0.932), and body fat percentage (r = 0.961). In contrast, height was negatively correlated with sprint ability (r = −0.407) and agility (r = −0.964), indicating a tendency that increased body size was followed by a decrease in acceleration ability and a change of direction. The resulting empirical norms are able to group the physical characteristics of players into five performance categories so as to provide an objective reference in the placement of player positions. The conclusion states that anthropometric characteristics and physical conditions provide meaningful information in the preparation of the position of young football players.